Evidence for the exclusive decay B(c)+- --> J/psi pi+- and measurement of the mass of the B(c)+- meson. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We report the first evidence for a fully reconstructed decay mode of the B(c)+- meson in the channel B(c)+- --> J/psi pi+-, with J/psi --> mu+ mu-. The analysis is based on an integrated luminosity of 360 pb(-1) in pp collisions at 1.96 TeV center of mass energy collected by the Collider Detector at Fermilab. We observe 14.6 +/- 4.6 signal events with a background of 7.1 +/- 0.9 events, and a fit to the J/psi pi+-mass spectrum yields a B(c)+- mass of 6285.7 +/- 5.3(stat) +/- 1.2(syst) MeV/c2. The probability of a peak of this magnitude occurring by random fluctuation in the search region is estimated as 0.012%.